PERLINDUNGAN HUKUM TERHADAP KECELAKAAN KERJA DITINJAU DARI SOSIOLOGI HUKUM - Musnimar, (Proceeding International Conference on Social Sciences, 2026)
The Riau Province Manpower and Transmigration Office receives approximately 10 to 15 complaints related to employment cases every day, originating from various business entities, large companies, medium enterprises and Small and Medium Enterprises. The increase in the number of incoming cases occurs due to the increasing number of Companies in Riau Province and the fact that many Companies have not fully implemented the implementation of Occupational Safety and Health. Among the incoming complaints are those related to the non-registration of workers in the Workers' Social Security Program. Many complications and problems occur, including differences of opinion between each party, both workers, Companies and BPJS, which require the Determination of the Labor Inspectorate, especially related to Work Accidents and Occupational Diseases. In Law No. 4 of 2004 concerning SJSN, Companies that do not comply are subject to Administrative Sanctions, whereas previously through Law No. 3 of 1992 concerning Jamsostek, the sanctions for such violations were criminal sanctions and fines. The main problem is how is the protection of work accident insurance against the Change in sanctions for the implementation of labor social security from Criminal to Administrative Sanctions viewed from the sociology of law? The changes in sanctions place workers in a vulnerable position, as implementing these administrative sanctions requires a complicated process, requires significant time and financial resources, and does not provide significant legal impact to employers. Consequently, workers and their families lack legal